Redesain Penanganan Pelanggaran Tindak Pidana Pemilu 2024: Upaya Mewujudkan Keadilan - Surahman, Surahman; Supriyadi, Supriyadi; Purnamasari, Andi Intan; Rampadio, Hamdan; Muja'hidah, Muja'hidah (Universitas Semarang, 2023)
This research aims to analyze the obstacles in handling election crimes and find the ideal argumentation basis to be used as an improvement to the handling of election crimes. The current handling of election criminal offenses is affected by problems of substance and structure. In terms of substance, there are several articles that regulate elements that are difficult to prove, such as articles related to money politics, political dowries, and unscheduled campaigns, while in terms of structure, the existence of integrated law enforcement centers tends to differ with each other in the process of handling election criminal offenses, which has an impact on the discontinuation of handling election criminal offenses. In addition, there is a change in the personnel of investigators and prosecutors when the process of handling violations is ongoing. This research is normative research. The results of the research illustrate that the redesign of the handling of election criminal offenses is carried out with two approaches, namely first, Article 492, Article 494, Article 495 paragraph (1) and paragraph (2), Article 513, Article 515, Article 518, Article 545. Second, the redesign of the handling of electoral crimes through the enactment of the concept of the provisions of Article 486 paragraph (2) and paragraph (4) expressly in the pattern of handling electoral crimes by the Gakkumdu center by placing the span of control of the termination of the investigation and prosecution process through legal instruments issued by Bawaslu. Penelitian ini bertujuan untuk menganalisis kendala dalam penanganan tindak pidana Pemilu serta menemukan basis argumentasi yang ideal untuk digunakan sebagai perbaikan terhadap penanganan tindak pidana Pemilu. Penanganan pelanggaran tindak pidana Pemilu saat ini dipengaruhi oleh problematika subtansi dan struktur. Dari sisi substansi, terdapat beberapa pasal yang mengatur Unsur-unsur yang sulit dibuktikan semisal pasal terkait politik uang, mahar politik, dan kampanye luar jadwal, sedangkan dari sisi struktur, keberadaan sentra penegakan hukum terpadu cenderung saling berbeda pandangan dalam proses penanganan pelanggaran tindak pidana Pemilu, yang berdampak pada tidak dilanjutkanya penanganan pelanggaran tindak pidana Pemilu. Di samping itu pula, dalam terjadi pergantian personil penyidik dan penuntut di saat proses penanganan pelanggaran tengah berjalan. Penelitian ini merupakan penelitian normatif. Adapun hasil penelitian memberikan gambaran yakni redesain terhadap penanganan pelanggaran tindak pidana Pemilu dilakukan dengan dua pendekatan yakni pertama, Pasal 492, Pasal 494, Pasal 495 ayat (1) dan ayat (2), Pasal 513, Pasal 515, Pasal 518, Pasal 545. Kedua, redesain terhadap penanganan tindak pidana Pemilu melalui dengan memberlakukan konsep ketentuan Pasal 486 ayat (2) dan ayat (4) secara tegas pada pola penanganan tindak pidana Pemilu oleh Sentra Gakkumdu dengan menempatkan rentang kendali penghentian proses penyidikan dan penuntutan melalui instrument hukum yang dikeluarkan oleh Bawaslu.